AN EVALUATION OF PATIENT SATISFACTION WITH INPATIENT SERVICES AT UPTD COMMUNITY HEALTH CENTER OF MUMBULSARI, JEMBER REGENCY - Lutrianingsih, Lutrianingsih; Wardhani, Roro Aditya Novi; Saputra, Harmawan Teguh (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: Patient satisfaction is a crucial indicator of healthcare quality, serving as a benchmark for evaluating service performance in primary care institutions. This study examines how SERVQUAL dimensions affect inpatient satisfaction at UPTD Community Health Centers, Mumbulsari, Jember. Methods: Data were gathered once within a predetermined time frame from patients who had received inpatient care during the preceding three months using a cross-sectional, quantitative strategy. Ninety respondents made up the sample, which was chosen using a combination of purposive and incidental sampling methods and calculated using Ferdinand's formula. The five SERVQUAL dimensions were measured using a standardized questionnaire with a five-point Likert scale. SPSS-supported multiple linear regression was used to examine the data.Results: The findings showed that tangibles, responsiveness, empathy, and assurance all significantly and favorably impacted patient satisfaction, with assurance being the best predictor. Unexpectedly, there was a strong negative correlation between reliability and satisfaction, meaning that as reliability increased, patient satisfaction decreased. This result may indicate problems with measurement validity or reflect a mismatch with patient expectations. With an Adjusted R2 of 0.819, the regression model showed strong explanatory power, indicating that aspects of service quality had an important impact on patient satisfaction.Conclusion and suggestion: It is concluded that improving assurance, responsiveness, empathy, and tangibles should be prioritized in service delivery, while the negative reliability effect requires further investigation to refine measurement tools or manage patient expectations. These findings have practical implications for enhancing primary healthcare management, particularly in strengthening staff competence, service responsiveness, and facility standards to increase overall patient trust and satisfaction. Keywords: Inpatient Care, Patient Satisfaction, Public Health Center, SERVQUAL